PESAN EKOLOGI DALAM SENI MUSIK: ANALISIS SEMIOTIKA PADA LIRIK LAGU “ADEK” KARYA GRUP MUSIK NOSSTRESS - Ridwan, Mudji (Smart Education, 2025)
Abstract: This research is interesting, especially in songs that are often a medium of communication to convey social and environmental messages. The analysis of the song “Adek” by the music group Nosstress can dig deeper into the art of music used to raise ecological issues and balance. In the Indonesian context, the relevance of this message can be linked to local environmental issues, such as deforestation, pollution, climate change and pollution. This research aims to analyze the ecological balance message in the lyrics of the song “Adek” by the music group Nosstress and its relevance to the environment in Indonesia. Roland Barthes' semiotic approach is used by researchers to analyze the signs of environmental messages and ecological balance in the lyrics through two levels of meaning, namely denotation and connotation. The textual analysis method is used to describe and explain the meaning of song lyrics in depth. Literature Review is used by researchers as a data retrieval technique through books, notes, journal articles, media, YouTube with primary data, namely the lyrics of the song “Adek” by the music group Nosstress. The results showed that the song “Adek” describes ecological balance, where there is a reciprocal relationship between living things and their environment, and has relevance to environmental conditions in Indonesia. In addition, this song also functions as an effective ecological education medium in communicating sustainability values. From this song, it reflects the important role of music in the contemporary ecological movement. Keyword: Art and Environment; Ecological Balance; Nosstress; Semiotic Analysis. Abstrak: Penelitian ini menarik, terutama pada lagu yang sering menjadi media komunikasi untuk menyampaikan pesan sosial dan lingkungan. Analisis lagu “Adek” karya grup musik Nosstress dapat menggali lebih dalam tentang seni musik yang digunakan untuk mengangkat isu dan keseimbangan ekologi. Dalam konteks Indonesia, relevansi pesan ini dapat dikaitkan dengan masalah lingkungan lokal, seperti deforestasi, polusi, perubahan iklim, dan pencemaran. Penelitian ini bertujuan untuk menganalisis pesan keseimbangan ekologi yang ada di dalam lirik lagu “Adek” karya grup musik Nosstress dan relevansinya terhadap lingkungan di Indonesia. Pendekatan semiotika Roland Barthes dipakai oleh peneliti untuk menganalisis tanda-tanda pesan lingkungan dan keseimbangan ekologi di dalam lirik melalui dua level makna, yaitu denotasi dan konotasi. Metode analisis tekstual digunakan untuk menggambarkan dan menjelaskan makna lirik lagu secara mendalam. Literatur Review digunakan oleh peneliti sebagai teknik pengambilan data melalui buku, catatan, artikel jurnal, media, youtube dengan data primernya, yaitu lirik lagu “Adek” karya grup musik Nosstress. Hasil penelitian menunjukkan bahwa lagu “Adek” menggambarkan keseimbangan ekologi, di mana adanya hubungan timbal balik makhluk hidup dengan lingkungannya, serta memiliki relevansi dengan kondisi lingkungan di Indonesia. Selain itu, lagu ini juga berfungsi sebagai medium edukasi ekologi yang efektif dalam mengkomunikasikan nilai-nilai keberlanjutan. Dari lagu ini, mencerminkan peran penting musik dalam gerakan ekologi kontemporer.. Kata kunci: Analisis Semiotika; Keseimbangan Ekologi; Nosstress; Seni dan Lingkungan.